Postoperative Changes in Central Corneal Thickness and Intraocular Pressure in a Prospective Cohort of Congenital Cataract Patients. Issue 11 (November 2020) - Chang, Pingjun; Kou, Jiaojiao; Zhang, Bing; Wang, Jiajun; Tian, Tong; Zhao, Yun-e
Abstract : Purpose: To evaluate changes in central corneal thickness (CCT) and intraocular pressure (IOP) in children after surgery for congenital cataracts and to investigate the association between CCT and IOP. Methods: For this prospective observational cohort study, we recruited patients undergoing surgery for unilateral or bilateral congenital cataracts. CCT and IOP were measured before surgery and 1, 3, 6, 12, and 24 months after surgery. Results: Seventy-six children (152 eyes) were enrolled; 33 eyes were unaffected by cataracts, 77 were aphakic, and 42 were pseudophakic. In aphakic eyes, mean CCT increased by 31.14 ± 44.32 μm at 12 months postoperation and 33.09 ± 35.42 μm at 24 months postoperation; this increase was significantly higher than that in pseudophakic eyes 12 months after surgery (8.36 ± 19.91 μm; P < 0.001) and 24 months after surgery (0.31 ± 14.19 μm; P = 0.024). However, no significant differences in IOP were found between the different phakic states at 12 and 24 months postoperation ( P = 0.672 and P = 0.080, respectively). There were also no significant differences in CCT and IOP before and after surgery in the unaffected eyes. Conclusions: Mean CCT peaked at 12 months, and the mean IOP remained normal in both the aphakic and pseudophakic eyes during this study. CCT and IOP were positively correlated, regardless of the phakic status or age, a relationship which suggests that both parameters should be monitored closely in postsurgical patients for up to 12 months and in this time, may impact the ability to diagnose glaucoma.